Orthognathic Surgical Splint for correction of Skeletal Class III Malocclusion: A Multidisciplinary Clinical Approach - Sardar, Charushila; Mistry, Gaurang; Vidhi Karia, Ankita Chitnis; Randhawa, Nimrat Kaur; Vaity, Swapnita (Journal of Neonatal Surgery, 2025)
Skeletal Class III malocclusion presents significant functional and esthetic challenges, often necessitating orthognathic surgical intervention. This case report details the conventional fabrication of an orthognathic surgical splint to assist mandibular repositioning in a young adult male undergoing bilateral sagittal split osteotomy. A coordinated approach between the departments of Orthodontics, Oral Surgery, and Prosthodontics enabled accurate diagnosis, pre-surgical decompensation, and model surgery on a semi-adjustable articulator. Using facebow transfer, split-cast mounting, and mock mandibular setback, a surgical splint was fabricated in clear acrylic to guide intraoperative alignment of the jaws. The splint facilitated precise mandibular positioning during surgery and ensured the transfer of the planned occlusion to the operating field. Postoperative healing was uneventful, and final occlusion was refined through orthodontic finishing. This case highlights the continued relevance of conventional techniques in achieving successful orthognathic outcomes when implemented through meticulous planning and interdisciplinary collaboration.